A Modification of the Frechet Distance for Nonnisomorphic Trees - Vodolazskiy, Ye.V. (Control systems & computers, 2021)
The paper presents a modification of the Frechet distance for nonisomorphic trees. While the classical Frechet distance between nonisomorphic trees is undefined, a new measure called similarity of a tree to a reference tree is given that is defined for a wider class of trees. A polynomial time algorithm is given for determining whether similarity of one tree to another is less than a given number. Ціль статті. Необхідно розробити метод порівняння дерев, ідеологічно близький до метрики Фреше, але виз- начений для пар неізоморфних дерев. Результати. У статті запропоновано модифікацію метрики Фреше для неізоморфних дерев. Нова числова характеристика названа близькістю дерева до еталону і визначена в тому числі для деяких класів пар неізоморфних дерев. Запропоновано поліноміальний алгоритм розпізнавання того, що одне дерево є близьким до іншого з точністю до заданого числа.